2021
DOI: 10.1002/nano.202000272
|View full text |Cite
|
Sign up to set email alerts
|

Microporosity mediated proliferation of preosteoblast cells on 3D printed bone scaffolds

Abstract: Microporous structure plays a significant role in bone tissue engineering, to influence inductive bone formation and elevate bone ingrowth inside microporous scaffolds. We hereby fabricated microporous scaffolds by 3D printing with mixture of porogens and photopolymerizing resin. Our method can tune the microporosity of scaffolds from 0% to 36% by varying the porogen concentration in the inks from zero to 60 vol%. The microporosity and microspore size of scaffolds can affect in vitro expansion of preosteoblast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…However, calcite formation is not desirable, as the bioactivity of calcite is based on its transformation to HA. [39,40,104,105] Raman spectra of both scaffolds (Figure S14, Supporting Information) further confirmed HA formation showing the emergence of a strong peak at 962 cm −1 (𝜈 sym(OPO) ) after 7 and 14 days of SBF immersion.…”
Section: Bioactivity Of the Scaffoldsmentioning
confidence: 75%
See 3 more Smart Citations
“…However, calcite formation is not desirable, as the bioactivity of calcite is based on its transformation to HA. [39,40,104,105] Raman spectra of both scaffolds (Figure S14, Supporting Information) further confirmed HA formation showing the emergence of a strong peak at 962 cm −1 (𝜈 sym(OPO) ) after 7 and 14 days of SBF immersion.…”
Section: Bioactivity Of the Scaffoldsmentioning
confidence: 75%
“…However, calcite formation is not desirable, as the bioactivity of calcite is based on its transformation to HA. [ 39,40,104,105 ]…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…By using water-in-poly­(dimethylsiloxane) (PDMS) emulsion templating, Malaquin fabricated highly interconnected porous polymer structures for three-dimensional (3D) cell cultures . Recently, we reported the successful 3D printing of porous bioscaffolds by combining DLP printing and porogen templating . The results showed that a macroporous structure larger than 200 μm could be achieved through 3D printing while the microporous structure (from nanometer to micrometer) could be controlled by the porogen concentration.…”
Section: Introductionmentioning
confidence: 99%